Behavioral Mechanisms and Psychopathology : Advancing the Explanation of Its Nature, Cause, and Treatment - Salzinger, Kurt; Serper, Mark R. (American Psychological Association, 2009)
"Mental health diagnosticians face a great challenge when exploring the presenting symptom of aberrant behavior, particularly in tracing such behavior to its source, and especially when such aberrant behavior involves no obvious biological site. In short, reliance on biological causes alone may be necessary to explain some aberrant behavior, but it is in any case not sufficient. The identification of the offending behavior alone is not sufficient either. We need to identify the variables that control it. For this purpose, we need to examine the behavioral mechanisms underlying the various behavioral disorders. Behavioral mechanisms fundamentally elucidate the nature of the psychopathology. Whether to enhance theoretical understanding or improve clinical efficacy, emotional and behavioral problems must be understood in terms of the controlling variables (the behavioral mechanisms). Examination of the behavioral mechanisms that mediate psychological disturbances is crucial for a complete understanding of the origin, maintenance, treatment, course, and symptomatology of any mental disorder. We asked the authors of the chapters in this volume to examine in turn the behavioral mechanisms that mediate (explain?) cause and effect for a variety of behavioral disorders and discuss the treatments that result from understanding these mechanisms. Each contributor or group of contributors to this volume responded to our charge to examine the behavioral mechanism underlying a particular form of psychopathology in terms of its own reinforcement history. That charge was given to these contributors on the basis of the fact that they were the experts and that they thus would be able to provide the readersstudents, scholars, and clinicians alikewith the most interesting and useful information. As the pages of this book reveal, behavioral mechanisms are multifaceted and allow the clinician and the researcher to reveal even more links in the chain of psychological functions that explain howand, more important, whypsychopathology is produced"--Introduction. (PsycINFO Database Record (c) 2009 APA, all rights reserved).